A STUDY OF PSYCHOLOGICAL CONFLICT AS A LESBIAN IN ANNIE ON MY MIND NOVEL BY NANCY GARDEN - Sella Damayanti (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2016)
In life, there are so many problems. Problems also happen in novel. We find various kinds of problems in novel which reflect the main characters’ daily life. The problems are sometimes in the form of psychological conflict. this kind of conflict is harder to solve especially for minority people such as lesbian. It is interesting to study about psychological conflict in novel, especially in Nancy Garden novel entitled Annie On My Mind. The novel is about Liza Winthrop as the main character faces her problem as a lesbian. This novel also was banned and burnt because Nancy garden was the first author for young adults to create a lesbian love story. Therefore, the researcher has been interested in studying this problem by formulating three research problems such as: (1) How is psychological background of Liza Winthrop as the main character in Annie On My Mind novel by Nancy Garden? (2) What are psychological conflicts that Liza Winthrop got when she realized that she fall in love with Annie Kenyon in Annie On My Mind novel by Nancy Garden? (3) How Liza Winthrop character in the Annie On My Mind novel by Nancy Garden overcomes her psychological conflict ? The research design which used in this research is descriptive qualitative research since the researcher intends to describe psychological backgorund, psychological conflict, and the way overcome the conflict. The data in this research analyzed into six steps, i.e data collection, data analysis, data reduction, data display, conclusion drawing, and data reportation. The researcher found there are five of Liza’s Winthrop character or psychological background that is formed based on her life environment. Those are introvert, masculin, responsible, idealis, and kind-heart person. Those Liza Winthrop’s psychological background influence Liza in overcome her psychological conflict which there are two of the most of psychological conflict faced by her, they are approach-approach conflict and double approach-avoidance conflict. Finally, the researcher really hopes for the student to learn fiction deeply and enjoyed analyzing literary works. And for the lecturer in English Literature Department, lecturer can give explanation about analyzing another aspect in the literary works in order students will not bored in learning or studying fiction. Last, but not least, for the further researcher, they could take different way in analyzing the literary works.